1990
DOI: 10.1172/jci114422
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fate of L-arginine in relation to microbiostatic capability of murine macrophages.

Abstract: L-arginine is required for the fungistatic action of murine macrophages in vitro. To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
201
0
1

Year Published

1992
1992
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(211 citation statements)
references
References 39 publications
(37 reference statements)
4
201
0
1
Order By: Relevance
“…The apparent K m of NO synthesis by intact cells for extracellular arginine is approx. 73-150 µM [187,188], which is within the range of the K m values of the arginine transport systems (100-150 µM) [165] and of plasma arginine concentrations (Table 1). Immunohistochemical studies [189] demonstrated that CAT-1, eNOS and caveolin are co-localized in plasma-membrane caveolae, suggesting a preferential channelling or directed delivery of extracellular arginine to eNOS, as proposed previously [174].…”
Section: ) Complete Oxidation Of Arginine-derived 2-oxoglutarate Osupporting
confidence: 60%
See 1 more Smart Citation
“…The apparent K m of NO synthesis by intact cells for extracellular arginine is approx. 73-150 µM [187,188], which is within the range of the K m values of the arginine transport systems (100-150 µM) [165] and of plasma arginine concentrations (Table 1). Immunohistochemical studies [189] demonstrated that CAT-1, eNOS and caveolin are co-localized in plasma-membrane caveolae, suggesting a preferential channelling or directed delivery of extracellular arginine to eNOS, as proposed previously [174].…”
Section: ) Complete Oxidation Of Arginine-derived 2-oxoglutarate Osupporting
confidence: 60%
“…Ornithine\urea production is the predominant route of arginine catabolism in unactivated rat endothelial cells [200,290], but NO production predominates when endothelial cells are stimulated with the appropriate combination of cytokines [200]. NO\citrulline synthesis represents the vast majority of arginine metabolism in rat macrophages [223], but ornithine\urea production dominates in murine macrophages [187,254,291]. These observations reflect the fact that arginase activity is greater in murine macrophages than in rat macrophages [201,292].…”
Section: Nosmentioning
confidence: 99%
“…In activated murine macrophages only 30% of cellular L-arginine metabolism occurs via NO synthase (Granger et al, 1990), though there is disagreement as to whether the flux of arginine to ornithine via arginase is concomitantly enhanced in activated macrophages (Benninghoff et al, 1991;Sato et al, 1992). We found increases in intracellular ornithine in J774 cells generating nitrite (Table 1) with negligible changes in extracellular ornithine (Table 2).…”
Section: Discussionmentioning
confidence: 76%
“…Expression of this enzyme is time-dependent, known to involve de novo protein synthesis and can be inhibited by glucocorticoids such as dexamethasone (Di Rosa et al, 1990;Assreuy & Moncada, 1992). The sustained production of NO is critically dependent on the presence of extracellular arginine (Drapier & Hibbs, 1988;Granger et al, 1990;Takema et al, 1991;Bogle et al, 1992a;Assreuy & Moncada, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…pneumophila by a murine macrophage cell line, RAW 264.7 in vitro [28]. NO is generated via nitric oxide synthase, which uses L-arginine as sole substrate to produce citrulline and NO, which gives rise to nitrate and nitrite [9][10][11].…”
Section: Introductionmentioning
confidence: 99%